Rare communication between ulnar nerve and MACN: A case report - Amit Kumar Vyas; Sayantani Misra (Journal of Orthopaedic Reports, 2024)
Background: There are very few reports of abnormal connections between medial antebrachial cutaneous nerve(MACN) and ulnar nerve(UN) of the upper extremity. This article describes an atypical ulnar nerve and medial antebrachial cutaneous nerve connection that was seen during an ulnar nerve transposition for tardy ulnar nerve palsy. Case report: A 28-years-old male presented with claw hand of left side. He reported feeling weaker in his hands while exercising, as well as medial sided elbow pain and ulnar sided hand numbness. Transposition of ulnar nerve anteriorly was difficult, as intraoperatively an ulnar nerve branch was found to be continuing towards the medical antebrachial cutaneous nerve. The branch was divided in order to transpose the ulnar nerve anteriorly. The recovery period was uneventful and no further complications were noted. Conclusion: These anatomical variations should be considered when performing upper limb surgeries, since abnormal connections may cause misidentification of the nerve, which may result in damage or inadequate treatment.